Management of atrial fibrillation-flutter: uptodate guideline paper on the current evidence. Issue 5 (3rd September 2018) - Shah, Syed Raza; Luu, Sue-Wei; Calestino, Matthew; David, John; Bray, Christopher
ABSTRACT: The term 'flutter' and 'fibrillation' were first coined to differentiate the differences between fast, regular contractions in Atrial Flutter (AFLUT) with irregular, vermiform contractions of Atrial Fibrillation (AFIB). Management of these two diseases has been a challenge for physicians. Rate control (along with rhythm control) is the first line of management for symptomatic AFIB/AFLUT with Rapid Ventricular Rate (RVR). In some situations, atrial rhythms may not be well controlled by these anti-arrhythmic drugs, making cardioversion to sinus rhythm necessary. Anti-coagulation therapy in both the disease population is essential. Catheter ablation is an effective treatment option in certain patients that have AFIB/AFLUT refractory to medical management. Newer techniques like left atrial appendage (LAA) has been developed and is a highly attractive concept for the future in the management of AFIB/AFLUT. Newer novel drugs targeting specific ion channels are approaching the stages of clinical investigation. However, while advances in technologies have helped elucidate many aspects of these diseases, many mysteries still remain. This literature review serves as one of the guideline papers for current up-to-date management on both AFIB and AFLUT.